The Effects of Perinatal Oxycodone Exposure on Behavioral Outcome in a Rodent Model - Sithisarn, Thitinart; Legan, Sandra J.; Westgate, Philip M.; Wilson, Melinda; Wellmann, Kristen; Bada, Henrietta S.; Barron, Susan (Frontiers in Pediatrics, 2017)
Opiate addiction is now a major public health problem. Perinatal insults and exposure to opiates such as morphine in utero are well known to affect development of the hypothalamic-pituitary-adrenal (HPA)-axis of the offspring adversely and are associated with a higher risk of developing neurobehavioral problems. Oxycodone is now one of the most frequently abused pain killers during pregnancy, however limited data are available regarding whether and how perinatal oxycodone exposure (POE) alters neurobehavioral outcomes of the offspring. We demonstrated that exposure to 0.5 mg/kg/day oxycodone in utero was associated with hyperactivity in adult rats in an open field. No significant effects of POE were detected on isolation induced ultrasonic vocalizations in the early postnatal period or on learning and memory in the water maze in adult offspring. Our findings are consistent with hyperactivity problems identified in children exposed to opiates in utero.